PENERAPAN PRICING STRATEGY DALAM MANAJEMEN BISNIS PADA UMKM (STUDI KASUS KOPI JANJI JIWA) - Irma Shantilawati; Annisa Anindya; Ibnu Suryadi (POLITEKNIK LP3I JAKARTA, 2024)
In the current era of digitalization, customers have a lot of literacy in knowing, accessing and easily comparing information about products and prices from various competitors so that customers can search for and decide which products to buy according to their wishes at the lowest price. In accordance with its mission, Kopi Janji Jiwa aims to introduce the quality taste of local Indonesian coffee to the public. One of the characteristics of Kopi Janji Jiwa is its relatively pocket-friendly prices. This is because Kopi Janji Jiwa itself targets the middle class as its main target. Apart from that, Kopi Janji Jiwa also implements production for the mass market so that product prices are adjusted to standards that apply to the wider community, not to certain groups. The problem that often occurs in every UMKM in Indonesia is that many UMKM do not calculate production costs and are inaccurate in determining selling prices. As a result, it causes losses and has to sell products at a loss. Therefore, UMKM must pay attention to choosing the type of pricing strategy that will be implemented. This research is intended to determine the extent of the influence of implementing pricing strategies in business management in UMKM (Case Study of Kopi Janji Jiwa). Key words: Pricing Strategy, Management of Business and UMKM